2022
DOI: 10.1038/s41419-022-05514-0
|View full text |Cite
|
Sign up to set email alerts
|

DC vaccines loaded with glioma cells killed by photodynamic therapy induce Th17 anti-tumor immunity and provide a four-gene signature for glioma prognosis

Abstract: Gliomas, the most frequent type of primary tumor of the central nervous system in adults, results in significant morbidity and mortality. Despite the development of novel, complex, multidisciplinary, and targeted therapies, glioma therapy has not progressed much over the last decades. Therefore, there is an urgent need to develop novel patient-adjusted immunotherapies that actively stimulate antitumor T cells, generate long-term memory, and result in significant clinical benefits. This work aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 85 publications
0
23
0
2
Order By: Relevance
“…To improve prognostic and predictive survival power in GBM patients, researchers [ 69 , 91 92 , 94 95 , 97 , 109 , 131 , 137 138 , 144 , 147 , 172 , 186 , 189 , 195 , 197 , 200 , 222 , 242 , 251 , 253 ], identified a panel of 2, 3, 4, 6,7, 8, 13, or 14 genes using mRNA expression datasets. They established a risk score model that performed well in survival prediction.…”
Section: Discussionmentioning
confidence: 99%
“…To improve prognostic and predictive survival power in GBM patients, researchers [ 69 , 91 92 , 94 95 , 97 , 109 , 131 , 137 138 , 144 , 147 , 172 , 186 , 189 , 195 , 197 , 200 , 222 , 242 , 251 , 253 ], identified a panel of 2, 3, 4, 6,7, 8, 13, or 14 genes using mRNA expression datasets. They established a risk score model that performed well in survival prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers investigated the efficacy of dendritic cell vaccines loaded with glioma cells undergoing immunogenic cell death induced by photosens-based PDT and identified a four-gene signature associated with overall survival of glioma patients. The results suggest that this approach has the potential to improve glioma therapy by inducing Th17 immunity and predicting patient outcomes ( 46 ).…”
Section: Immuno Vaccines Combined With Pdtmentioning
confidence: 99%
“…The use of chemotherapeutic drugs that induce ICD can attract γδT17 cells in the TME, thereby facilitating subsequent cognate anticancer T cell responses ( 160 ). Building on this initial work, it has been shown that a dendritic cell (DC) vaccine, based on whole glioma GL261 cell lysates pulsed with ICD-induced photodynamic therapy, has an activated Th17 signature characterized by an increased expression level of Tgfb-3, IL-6, and IL-23a genes ( 114 ) ( Figure 1 ). This approach demonstrates prophylactic and therapeutic efficiency in a murine orthotopic glioma model ( 114 ).…”
Section: An Emerging Role Of Th17 Cells In Glioma Microenvironmentmentioning
confidence: 99%